Comitê estadual da educação do campo: a materialização da luta política no âmbito da educação do campo no Paraná - Seganfredo, Katia Aparecida (2014)
This thesis is the result of research that had as its central objective to analyze the relationship between government and civil society organizations within the field of education in the state of Paraná. The guiding research question was: How does the relationship between government and civil society and how this relationship emerges as a political struggle from the State Committee of Countryside Education? This is qualitative research composed of bibliographic study, document analysis, semistructured interviews and field work. The text is organized into four chapters. Discussed in the first chapter the configuration of the Brazilian State and the implication in the educational process of the peoples of the field. In the second chapter we bring the Movement of education countryside in Paraná and the State Committee of Countryside Education. In the third chapter, we look input from the Gramscian, analyze the relationship between civil society and government in the discussion of country side in the state of Paraná and finally, in the fourth chapter we approach the State Committee of Countryside Education as the materialization of the struggle policy in the sphere of country side in the state of Paraná. Is observed that arising from the collective struggle of organized civil society can build meaningful experiences in the education sector. Considering the complexity of the capitalist state, these experiences are as expressive strategies against hegemonic in the class struggle.